Progress in the fight against corruption in Asia and the Pacific : (Asian Development Bank, 2001)
Combating corruption is becoming a major concern among the governments in the Asia-Pacific region. One strategy is to develop effective worldwide cooperation in corruption prevention. This book brings together the insights of leading actors in the fight against corruption and presents the progress made in the region. It encourages cooperation among countries in the Asia-Pacific to develop more effective measures to combat corruption.